A Giant Primary Mediastinal Teratocarcinoma in a Male Adult - Muneera Al-Khalifa; Sara Alsaad; Habib Al-Tareef; Zaid Arekat; Abdulla Darwish (Case Reports in Surgery)
Germ cell tumors (GCTs) arise along the midline, in which 50-70% of extragonadal GCTs occur in the mediastinum. Malignant GCTs are more common in males, while benign GCTs occur equally in both males and females. This report presents a case of a giant primary mediastinal nonseminomatous GCT resected from a 35-year-old male who presented with dyspnoea and tightness in the chest. Thorough investigations including a chest MRI were done. It showed a 21×19×15 cm tumor. Thus, surgical resection of the tumor through a midline sternotomy was done. Histopathological analysis diagnosed the tumor as a primary mediastinal teratocarcinoma with a sarcomatous component. Eighteen-month follow-up showed no tumor recurrence. Mediastinal teratocarcinoma is a rare and life-threatening germ cell tumor. Studies recommend the use of chemotherapy prior to resection as an important step in its management. Close and regular follow-up postsurgical resection is advised.